Sex differences in cued fear discrimination: a combined behavioural, computational and electrophysiological study - Day, Harriet Laura Lavinia (2018)
Women are up to twice as likely to suffer from post-traumatic stress disorder (PTSD) than men. Failure to discriminate between cues predicting threat and safety is associated with PTSD, yet sex differences in fear discrimination remain poorly understood. Here, we examined sex differences in auditory fear discrimination in rats using a combination of behavioural, computational and electrophysiological methods. In the initial behavioural study, males and naturally cycling females underwent 1-3 days of discrimination training, consisting of pairings of one tone (CS+) with shock and presentations of another tone (CS-) alone. After one day of training, females, but not males, discriminated between the CS+ and CS-. With 2-3 days of training, however, males discriminated and females generalised between the CS+ and CS-. Further testing also revealed that males successfully encode the CS- as a safety signal, whereas females do not. Using reduced computational models, we investigated how both ‘discrimination’ and ‘generalisation’ phenotypes can be generated in silico. We achieved this through a simulation of neural activity produced via ‘fear’ and ‘safety’ neural sub-populations of the basolateral amygdala (BLA) in response to CS+ and CS- cues. By using a model representation of extended fear discrimination training and retrieval, we found that generalisation between the CS+ and CS- could be produced from reduced inhibition, or increased excitation, of fear neurons. Due to their involvement in regulating learned fear, we additionally aimed to investigate the roles of the prelimbic (PL) and infralimbic (IL) cortices of themedial prefrontal cortex in fear discrimination. By concurrently recording activity from the PL, IL and BLA in awake behaving animals during retrieval of the CS+ and CS- after extended discrimination training, we examined the individual contributions and functional interactions of these regions during this learning paradigm. We found that, in males, the PL showed an increase in power at both theta (4-12 Hz) and gamma (30-120 Hz) frequencies during presentations of the CS- compared to the CS+, whereas this increase was largely absent in females. Taken together, these results indicate that, while females show fear discrimination with limited training, they generalise with extended training. We hypothesised that this generalisation in females is likely due to impaired safety learning, which may result, in part, from sex differences in the neural circuitry underlying fear discrimination.